2015
DOI: 10.1021/acs.jpcc.5b01920
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Co2+-Doped PbSe Nanocrystals in Chalcogeneide Glass Matrix

Abstract: Semimagnetic chalcogeneide Pb 1−x Co x Se nanocrystals were successfully synthesized by a fusion protocol in a glass matrix and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), magnetic force microscopy (MFM), and optical absorption (OA) techniques. XRD, TEM, and MFM measurements show that the as-produced Pb 1−x Co x Se magnetic nanocrystals are single phases, nanosized, and crystallized in rock-salt structures. The OA spectra and crystal field theory indicate that part of Co 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In order to identify the symmetrical environment in which the Mn 2+ ions may be found in the ZnO NCs, adjustments will be made to the optical absorption spectra of the samples (ZnO, 0.5Mn, 1.0Mn and 9Mn) shown in Figure 1(b). These adjustments are made in the positions of absorption of Mn 2+ ions, making possible the use of the crystalline field theory (CFT) based on the crystalline field strength parameters ∆ and Racah B, both calculated with help of Tanabe-Sugano diagram (Figure 1(c)) [20]. From the OA spectra of the NCs of Zn: xMn, based on the Tanabe-Sugano diagram, the energies of the characteristic electronic transitions of Mn 2+ : 6 A 1 ( 6 S) → 4 T 1 ( 4 G) (691 nm), 6 A 1 ( 6 S) → 4 T 2 ( 4 G) (590 nm), 6 A 1 ( 6 S) → 4 T 2 ( 4 D) (482 nm), and 6 A 1 ( 6 S) → 2 E ( 2 I) (410 nm) (Figure 1b) subtly permitted by spin-orbit coupling were effectively described by the Racah B parameter (559 cm −1 ) and the crystalline field division (∆ = 5464 cm −1 ) [21,22].…”
Section: A Study In Function Of Mn Concentration In Zno Nanocrystals: Solubility and Mn 2+ Ions Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to identify the symmetrical environment in which the Mn 2+ ions may be found in the ZnO NCs, adjustments will be made to the optical absorption spectra of the samples (ZnO, 0.5Mn, 1.0Mn and 9Mn) shown in Figure 1(b). These adjustments are made in the positions of absorption of Mn 2+ ions, making possible the use of the crystalline field theory (CFT) based on the crystalline field strength parameters ∆ and Racah B, both calculated with help of Tanabe-Sugano diagram (Figure 1(c)) [20]. From the OA spectra of the NCs of Zn: xMn, based on the Tanabe-Sugano diagram, the energies of the characteristic electronic transitions of Mn 2+ : 6 A 1 ( 6 S) → 4 T 1 ( 4 G) (691 nm), 6 A 1 ( 6 S) → 4 T 2 ( 4 G) (590 nm), 6 A 1 ( 6 S) → 4 T 2 ( 4 D) (482 nm), and 6 A 1 ( 6 S) → 2 E ( 2 I) (410 nm) (Figure 1b) subtly permitted by spin-orbit coupling were effectively described by the Racah B parameter (559 cm −1 ) and the crystalline field division (∆ = 5464 cm −1 ) [21,22].…”
Section: A Study In Function Of Mn Concentration In Zno Nanocrystals: Solubility and Mn 2+ Ions Localizationmentioning
confidence: 99%
“…Furthermore, the p-d and spin-orbit interactions in an asymmetric tetrahedral coordination complex [CoS 4 ] 6− provide a higher intensity for 3d-3d transitions [14,15,20,42]. Therefore, the exotic properties of these new materials called diluted magnetic semiconductors (DMS) NCs are linked to the nature of the sp-d exchange interaction that occurs between the charge carriers of the Bi 2 S 3 semiconductor bands around the electrons in the central metal ion orbital (Co 2+ ) with 3d 7 electronic configuration (spin) 3d 7 (S = 3/2) [15,20,36,42]. For Bi 2-x Co x S 3 NCs, the spin allowed transitions 4 A 2 ( 4 F) → 4 T 1 ( 4 F) and 4 A 2 ( 4 F) → 4 T 1 ( 4 P) are obtained with the energy value of the barycenter for a normal distribution of the bands observed in the spectrum absorption in the range of 0.62-1.24 eV and 1.70-2.60 eV.…”
Section: Effects Of Symmetry and Concentration Of Cobalt-doped Bi 2 S 3 Nanocrystals Embedded In Host Glass Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] In this scenario, the fusion‐nucleation synthesis methodology is suitable for the formation of DMS NC having a glass matrix as a host, in which they show good thermal stability [ 19 ] and corrosion resistance. [ 20 ] As an example, the DMS NC is grown in a glass matrix that has optical and magnetic properties dependent on the concentration of transition metals, such as Bi 2 − x Mn x S 3 , [ 21 ] Bi 2 − x Co x S 3 , [ 22 ] Bi 2 − x Fe x S 3 , [ 23 ] Bi 2 − x Mn x Te 3 , [ 24 ] Bi 2 − x Cr x Te 3 , [ 25 ] Cd 1 − x Mn x S, [ 26 ] Pb 1 − x Mn x S, [ 27 ] Pb 1 − x Co x Se, [ 28 ] and Sb 2 − x Mn x S 3 . [ 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…For all the systems studied so far it has been found that the ground state of the magnetic ion is significantly influenced by the local strain present in a quantum dot. Such an effect is of particular importance for future applications in solotronics (optoelectronics based on single dopants [17]) and spintronics based on magnetic QDs [18][19][20][21][22][23][24][25][26][27][28]. The effect of strain may be demonstrated as beating in the coherent precession of the single magnetic ion spin [29], as changes of occupation and energy of levels corresponding to various projections of the ion spin [1,7,15], or even as a change in the character of the Fe 2+ ion ground state, from nonmagnetic in bulk to magnetic in a QD [13].…”
Section: Introductionmentioning
confidence: 99%